2012
DOI: 10.1111/j.1439-0272.2012.01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mutations in the synaptonemal complex protein 3 (SYCP3) gene among azoospermic infertile male patients in the Turkish population

Abstract: To investigate possible mutations and/or single nucleotide polymorphisms in the synaptonemal complex protein 3 (SYCP3) gene among nonobstructive azoospermic infertile males in a Turkish population, 75 nonobstructive azoospermic infertile male patients were included in the study. These patients were unrelated to each other and had 46,XY chromosome structure without Y microdeletion. In addition, 75 individuals whose fertility was proven by reproduction were enrolled in the study as controls. Nine exon deep intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…As a first example, a heterozygous frameshift mutation in exon 8 of SYPC3 escaping nonsense‐mediated RNA decay and leading to a truncated, but stable protein was previously described in two unrelated patients with azoospermia as a result of meiotic arrest (Miyamoto et al., ). It had since then been assumed that such SYCP3 mutations result in a very homogeneous phenotype, but no other patients with azoospermia and mutations in SYCP3 could be identified in other studies (Gurkan, Aydin, Kadioglu, & Palanduz, ; Martinez, Bonache, Carvajal, Bassas, & Larriba, ; Stouffs, Lissens, Tournaye, Van Steirteghem A, & Liebaers, ). Here, we identified a new heterozygous frameshift mutation in exon 7 of SYCP3 that will likely result in nonsense‐mediated RNA decay in a patient with oligozoospermia in combination with teratozoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…As a first example, a heterozygous frameshift mutation in exon 8 of SYPC3 escaping nonsense‐mediated RNA decay and leading to a truncated, but stable protein was previously described in two unrelated patients with azoospermia as a result of meiotic arrest (Miyamoto et al., ). It had since then been assumed that such SYCP3 mutations result in a very homogeneous phenotype, but no other patients with azoospermia and mutations in SYCP3 could be identified in other studies (Gurkan, Aydin, Kadioglu, & Palanduz, ; Martinez, Bonache, Carvajal, Bassas, & Larriba, ; Stouffs, Lissens, Tournaye, Van Steirteghem A, & Liebaers, ). Here, we identified a new heterozygous frameshift mutation in exon 7 of SYCP3 that will likely result in nonsense‐mediated RNA decay in a patient with oligozoospermia in combination with teratozoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…This gene encodes a structural component of the axial and lateral parts of the synaptonemal complex. The synaptonemal complex mediates the pairing and synapsis of homologous chromosomes at the pachytene stage, and several reports have shown mutations of this gene to be associated with azoospermia in man and susceptibility to pregnancy loss444546. Thus, the interruption of SYCP3 may have altered expression of the protein, leading to synaptonemal complex dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, carried out in 22 Mediterranean infertile men with azoospermia or severe oligozoospermia (excluding men with chromosomal aberrations or Y-chromosome microdeletions [Chandley, 1998;Stahl et al, 2010]), was also unable to find SYCP3 mutations [Martínez et al, 2007]. A more recent work involving 75 Turkish men with nonobstructive azoospermia (excluding Y microdeletions) also failed to detect SYCP3 mutations, only identifying polymorphisms [Gurkan et al, 2012].…”
Section: Sycp3 Mutationsmentioning
confidence: 99%
“…Finally, it has been suggested that ethnicity may also play a role. Apparent discrepancies between the results of the different patient cohorts might be due to polymorphisms in the different populations [Martínez et al, 2007;Gurkan et al, 2012;Sazegari et al, 2014].…”
Section: Sycp3 Mutationsmentioning
confidence: 99%